Impact of Patient Preparation on the Diagnostic Performance of 18F-FDG PET in Cardiac Sarcoidosis: A Systematic Review and Meta-analysis. (July 2016) - Tang, Reuben; Wang, Jeffrey Tzu-Yu; Wang, Louis; Le, Ken; Huang, Yeqian; Hickey, Adam James; Emmett, Louise
Abstract : Purpose: 18 F-FDG PET/CT is a valuable diagnostic tool in the evaluation of cardiac sarcoidosis. Appropriate patient preparation is important because the diagnostic accuracy of this procedure depends on adequate suppression of physiologic glucose uptake. This systematic review and meta-analysis aims to assess the effect of different patient preparations on the diagnostic accuracy of 18 F-FDG PET/CT in cardiac sarcoidosis. Patients and Methods: We searched the PubMed/MEDLINE, Embase, and Cinicaltrials.gov databases. Sixteen studies (n = 559) were identified to be suitable for this systemic review. Studies were stratified according to fasting duration and means of physiologic suppression of 18 F-FDG by cardiac tissue, which involves the use of heparin infusion or high-fat, low-carbohydrate diet before imaging. Study quality was assessed using the QUADAS-2 tool. Forest plots of sensitivity and specificity were calculated in Review Manager 5.3, and a random-effects hierarchical summary receiver operating characteristic model was created using MetaDiSc. Meta-regression was performed to investigate sources of heterogeneity. Results: PET/CT had an overall Specificity of 0.75 (95% confidence interval [CI], 0.69–0.80) and specificity of 0.81 (95% CI, 0.76–0.85) for the diagnosis of cardiac sarcoidosis. This modest diagnostic accuracy was attributed to the inclusion of large single study in which a short fasting duration before scanning likely influenced its sensitivity. Its exclusion resulted in an overall sensitivity of 0.81 (95% CI, 0.76–0.86) and specificity of 0.82 (95% CI, 0.77–0.86). Meta-regression showed that the diagnostic odds ratio was significantly affected by fasting time and heparin administration before scanning ( P = 0.01, 0.02) but not with high-fat, low-carbohydrate diet ( P = 0.17). Conclusions: 18 F-FDG PET/CT plays an integral role in the diagnosis of cardiac sarcoidosis. Diagnostic accuracy is affected by fasting duration and means of cardiomyocyte glucose uptake suppression before scanning.